Synthesis, characterization and catalytic properties of a copper-containing polyoxovanadate nanocluster in azide–alkyne cycloaddition. Issue 9 (3rd May 2017) - Amini, Mojtaba; Bahadori Tekantappeh, Sajjad; Eftekhari-Sis, Bagher; Gohari Derakhshandeh, Parviz; Van Hecke, Kristof
Abstract: A copper-containing polyoxovanadate nanocluster, [(C2 H5 )4 N]4 [V8 Cu2 O24 ]∙2H2 O (1 ), was synthesized through reaction between the Cu(NO3 )2 ∙3H2 O and [(C2 H5 )4 N]4 VO3 in the molar ratio 1 : 4. Nanocluster1 was characterized by IR, elemental analysis, XRD, SEM, TEM, and X-ray crystallography. The catalytic activity of1 for the azide–alkyne cycloaddition of different terminal alkynes and organic azides generated in situ from sodium azide and different organic halides was tested. The protocol could afford the corresponding products in good to excellent yield at very low catalyst loadings (3.4 Mol%) under the optimized reaction conditions. Abstract :